INTERIOR FORMATION TRENDS OF MODERN ECONOMIC APARTMENTS WITH MINIMUM SQUARE - Кисіль, С. С. (Art and Design, 2018)
Identify the basic planning, artistic and aesthetic trends in the formation of modern small apartments interiors in multi-storey residential buildings. In the course of the study, methods were used to analyze domestic and foreign practice of designing, building and operating residential houses with economic small apartments, studying literary and normative documents, and the results of scientific research. Results. The socio-economic conditions established today in Ukraine are established and the urgent need for designing and building multi-storey residential buildings with economic apartments of the minimum permissible area is determined. The tendencies of formation of interiors of modern economic apartments with the minimum area on the basis of domestic and foreign experience of design and construction of this type of dwelling in Ukraine and in the world are revealed. On the basis of domestic normative documents on the design of residential buildings, the range of living permissible area per person has been analyzed and it’s determined that the total area of one-room small-apartment apartments can be taken from 18 to 29 m², while taking certain compensatory measures. Namely: reduction of the total area of bathrooms due to the use of shower cubicles instead of baths, which does not contradict the sanitary-hygienic requirements; organization of a kitchen-niche instead of a fully-fledged kitchen equipped with electric cookers using a forced exhaust ventilation system in it and in a combined bathroom; use of additional space by removing the doors in the rooms; The given recommendations for improvement of planning, aesthetic, ergonomic decisions of interiors of small-apartment apartments and suggestions on the choice of special furnishings for them. The recommendations are defined in parts: planning – expedient allocation of functional zones for sleep, physiological needs and depending on the existing living space of the dwelling, the organization of necessary additional zones and their association (general room with kitchen-niche; ergonomic solution of transit , passage zones in the house accessible to all categories of the population, with disabilities including; artistic and aesthetic solution – decoration of low-rise residential interiors with a choice of modern style solution, expedient Rehoboam palette and textiles, furniture – the use of eco-friendly furniture transformed to enhance the comfort of accommodation in apartments small area.